ANALISIS PENGARUH KUALITAS PELAYANAN JASA KEPENDIDIKAN TERHADAP KEPUASAN DAN LOYALITAS MAHASISWA MENGGUNAKAN STRUCTURAL EQUATION MODELING (STUDI KASUS DI JURUSAN MIPA UNSOED) - Supriyanto Supriyanto; Mutia Nur Estri; Agustini Tripena Br.Sb. (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2014)
Increasingly strong competition in intercollegiate and students who increasingly selective and knowledgeable require universities to continue to improve his ministry. Matter requires a knowledge of the conditions for this service, that has adapted to student expectations or not . This study aimed to determine the extent to which level the match between the expected service quality and perceived student at Department of Mathematics and Natural Sciences Unsoed and explain the influence of the five dimensions of service quality that is tangibles, reliability, responsiviness, assurance and empathy for student satisfaction and loyalty. Results of the study was assessment of the quality of student services at the Department of Mathematics and Natural Sciences Unsoed is perceived service quality is still below the expected service quality , perceived still not satisfactory. Five dimensions of service quality consisting of tangibles, reliability, responsiveness, assurance, and empathy, positive effect on student satisfaction. Satisfaction indirect influence on student loyalty and there is a direct influence of the five dimensions of service quality on loyalty through student satisfaction. Student loyalty translated in expressing positive things about the Department of Mathematics and Natural Sciences to others , recommending courses at the Department of Mathematics and Natural Sciences to the others, recruiting new employees from alumni, and ready to provide assistance if needed.